Assessing the impact of disaster drills on emergency nurses: development and validation of the Disaster Drills Effectiveness Questionnaire (DDEQ) - Majed Awad Alanazi (BMC Nursing)
Abstract Background Emergency nurses play a critical role in disaster response; however, their preparedness often remains suboptimal. Structured disaster drills are widely used to improve knowledge and skills, yet there is limited evidence on their effectiveness. Moreover, there is a lack of culturally relevant, psychometrically validated tools to assess disaster preparedness among nurses in non-Western contexts. Objectives This study aimed to develop and validate the Disaster Drills Effectiveness Questionnaire (DDEQ) as a culturally sensitive instrument for assessing the knowledge and skills of emergency nurses participating in disaster drills in Saudi Arabia. Methods A three-phase, cross-sectional design guided the development and validation of the DDEQ. Phase 1 involved item generation through literature review, expert input, and a two-round Delphi process, yielding a 28-item scale across two domains: knowledge and skills. Phase 2 focused on scale development and content validation (S-CVI/Ave > 0.90). A pilot study with 19 nurses assessed clarity and feasibility. Phase 3 involved psychometric testing using Exploratory Factor Analysis (n = 303) and Confirmatory Factor Analysis (n = 302), followed by reliability and validity analyses. Results Exploratory factor analysis supported a two-factor structure (knowledge and skills), accounting for 67.65% of total variance. Confirmatory factor analysis demonstrated excellent model fit (χ²/df = 1.735, RMSEA = 0.049, CFI = 0.968, TLI = 0.963). Internal consistency was high (Cronbach’s α = 0.977), with test-retest reliability (r = 0.747, p < 0.001) confirming temporal stability. Convergent and discriminant validity were established (AVE > 0.60, HTMT < 0.90). The DDEQ effectively captures emergency nurses’ disaster preparedness based on participation in disaster drills. Conclusion The DDEQ is a valid and reliable tool for evaluating the effectiveness of disaster drills in enhancing emergency nurses’ knowledge and skills. It offers a practical framework for healthcare institutions, educators, and policymakers to assess and improve disaster preparedness among nursing professionals. Clinical trial number Not applicable.